Gilda Joyce : the ladies of the lake / 2 - Allison, Jennifer (Gilda Joyce, 2006)
Having earned a scholarship to a private girls' high school, self-proclaimed psychic investigator Gilda Joyce investigates the circumstances surrounding the drowning death of a student whose ghost supposedly haunts the campus.